Hexaaquamagnesium 5-[1-(carboxylatomethyl)pyridin-1-ium-4-yl]tetrazol-2-ide chloride dihydrate - Zhang, Yu (International Union of Crystallography, 2011)
In the title compound, [Mg(H(2)O)(6)](C(8)H(6)N(5)O(2))Cl·2H(2)O, the Mg(II) ion is surrounded by six water molecules, exhibiting a slightly distorted octahedral coordination. The pyridine and tetrazole rings are nearly coplanar, forming a dihedral angle of 4.63 (3)°. The complex cations, zwitterionic organic anions, Cl(−) anions and uncoordinated water molecules are connected by O—H⋯O, O—H⋯N and O—H⋯Cl hydrogen bonds, leading to the formation of a three-dimensional network.